p-phenoxyphenol impaired male fertility by disrupting the testicular function and local microenvironment - Xiaojuan Han; Danni Jiang; Qianni Li; Pengfei Li; Lan Chao; Yang Yang (Ecotoxicology and Environmental Safety)
p-phenoxyphenol (PhOP) is an endocrine-disrupting chemical commonly used as an industrial raw material. It can be released either as a monomer or as a metabolite from products containing PhOP. PhOP has been reported to have estrogenic activity, but its reproductive toxicity effect on males remains unclear. In this study, a PhOP exposure model was constructed by gavage of 3, 30, and 100 mg/kg/d PhOP into ICR mice for 6 weeks. PhOP exposure decreased sperm motility and damaged testicular structure in mice. Oral exposure to PhOP notably inhibited cell proliferation, promoted cell apoptosis, and elevated oxidative stress levels in mice testis. Additionally, PhOP disrupts steroidogenesis and compromises the blood-testis barrier integrity. To assess its reproductive toxicity in vitro, we exposed GC-2, TM3, and TM4 cells to 0, 10, 20, and 40 μM PhOP for 24 hours. The findings revealed that PhOP reduced proliferation and triggered apoptosis and oxidative stress in GC-2 cells. In TM3 cells, PhOP exposure led to apoptosis and altered the expression of genes related to testosterone synthesis. Similarly, in TM4 cells, PhOP promoted apoptosis and disrupted the expression of genes associated with the blood-testis barrier. Finally, our study confirmed that PhOP significantly reduced sperm motility in human semen samples. In conclusion, PhOP induced male reproductive toxicity by their multifaceted toxicity on testis and sperm in mice, providing novel insights into the reproductive risks of PhOP to mammals.